2023
DOI: 10.1017/ice.2023.62
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers consistently overestimate the diagnostic probability of ventilator-associated pneumonia

Abstract: Objective: To assess the accuracy of provider estimates of ventilator-associated pneumonia (VAP) diagnostic probability in various clinical scenarios. Design: We conducted a clinical vignette-based survey of intensive care unit (ICU) physicians to evaluate provider estimates of VAP diagnostic probability before and after isolated cardinal VAP clinical changes and VAP diagnostic test results. Responses were used to calculate imputed diagnostic likelihood ratios (LRs), which were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…When comparing the pre-and post-protocol groups, we observed that a numerically larger percentage of patients post-implementation given antibiotics were considered to have probable HAP/VAP and a smaller percentage were given antibiotics with a classification of unlikely HAP/VAP (overall pneumonia comparison nonsignificant with a p value of 0.263). In the current landscape where ICU providers significantly over-diagnose nosocomial pneumonia, we hypothesize that the clear diagnostic criteria algorithm providers had to follow contributed to this numeric shift in patients receiving antibiotics who did not meet criteria for initiation [5]. The finding that only 80% of patients in the pre-protocol and 85% in the post-protocol group had cultures sent points to another challenge: patients who were not producing sputum or secretions in sufficient quantities were not able to have cultures obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the pre-and post-protocol groups, we observed that a numerically larger percentage of patients post-implementation given antibiotics were considered to have probable HAP/VAP and a smaller percentage were given antibiotics with a classification of unlikely HAP/VAP (overall pneumonia comparison nonsignificant with a p value of 0.263). In the current landscape where ICU providers significantly over-diagnose nosocomial pneumonia, we hypothesize that the clear diagnostic criteria algorithm providers had to follow contributed to this numeric shift in patients receiving antibiotics who did not meet criteria for initiation [5]. The finding that only 80% of patients in the pre-protocol and 85% in the post-protocol group had cultures sent points to another challenge: patients who were not producing sputum or secretions in sufficient quantities were not able to have cultures obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are specific criteria for HAP and VAP diagnosis, objective definitions are challenging, and various subjective criteria must often be considered [3,4]. The existing literature demonstrates that physicians consistently overestimate the diagnostic probability of VAP in the ICU [5,6].…”
Section: Introductionmentioning
confidence: 99%